Acute iron intoxication in pregnancy: case report - Sá,Maria Isabel (2015)
Acute intentional iron intoxication is an unusual scenario in the Obstetrics Emergency Department. However, it is the second most common overdose in pregnancy and it is associated with severe morbidity and mortality. We present a case of a 30-week pregnant woman with potential severe iron intoxication in the context of a suicide attempt.